HAKIKAT EVALUASI: Perspektif Filsafat Pendidikan Islam - Nuryamin, Nuryamin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
Generally in education and especially in school, assessment is meaningful to students, teachers and school it self. For students, there are two possibilities may occur, satisfied or unsatisfied. For teachers, it can be used to know whether or not student master the teaching material. It is also used to know whether or not the teaching method is effective. It may be argued that the teaching method and media are ineffective when most students get lower score. Finally, for school, evaluation may become a basis of improving good learning condition as a prerequisite of qualified school.